IDENTIFICATION OF CRACK IN REINFORCED CONCRETE BEAM SUBJECTED TO STATIC LOAD USING NON-LINEAR FINITE ELEMENT ANALYSIS - Halahla, Abdulsamee M. (Civil Engineering Journal, 2019)
Experimental testing was used widely as a means to investigate the behavior of these individual elements and the effects of concrete strength under different loading types. While this method represents real life responses, it is very time consuming and the use of materials can be quite costly. Recently, the use of finite element analysis (FEA) has increased due to advances in knowledge and the capabilities of computer hardware and software. The utilization of computer software to model the structural elements has become much faster and extremely cost-effective. The finite element software ANSYS 11.0 is used for modeling and analysis by conducting non-linear static analysis. This research work used nonlinear finite element analysis for a reinforced concrete beam in order to show the potential of the FEA for studying the behavior of reinforced concrete elements, and to understand their load-deflection response along with the crack evolution. For concrete a solid 65 element was used, while for the reinforcement steel bar link 8 elements were used. For the material constitutive model linear and multi-linear behavior for concrete were considered, while linear and bilinear behavior were considered for the reinforcement bar.  A reinforced concrete beam model is studied and compared with experimental data from the literature. The characteristic points on the load-deflection response curve predicted using finite element analysis, were compared to the theoretical limit (hand-calculated) results. Conclusions were then drawn as to the accuracy of using finite element modeling for the analysis of reinforced concrete elements. The results showed a good match to experimental and hand calculations.